Efficient metal-free N-doped mesoporous carbon catalysts for ORR by a template-free approach. (September 2016) - Ferrero, Guillermo A.; Fuertes, Antonio B.; Sevilla, Marta; Titirici, Maria-Magdalena
Abstract: A simple, cost-effective and scalable approach for the synthesis of N-doped mesoporous carbons that are effective as ORR catalysts is reported. The synthesis procedure involves two steps: a) production of mesoporous carbons using a template-free approach based on the carbonization of citrate salts of zinc and calcium, and b) N-doping by heat treatment in the presence of melamine. The resulting N-doped carbon possess a high specific surface area, a porosity made up exclusively of mesopores and a large amount of nitrogen functionalities (∼8–9 wt%). When used as an electrocatalyst for the oxygen reduction reaction (ORR), the metal-free carbon materials predominantly catalyze the 4 e − process, with an onset potential of 0.9 V ( vs. RHE) and a superior kinetic current density (∼17 mA cm −2 ) to that of Pt/C at ∼0.6 V under basic conditions. In addition, the developed catalysts show a higher stability than commercial Pt/C and excellent electrocatalytic selectivity against methanol crossover.